2011
DOI: 10.1002/dc.21409
|View full text |Cite
|
Sign up to set email alerts
|

Primary peripheral pulmonary adenoid cystic carcinoma: Report of a case diagnosed by fine needle aspiration cytology

Abstract: Adenoid cystic carcinoma (ACC) arising from anatomic sites other than the salivary gland is rare and those occurring in the lung are extremely rare. When arising from the lung, the tumor generally arises from extrapulmonary bronchi, originating from bronchial glands. Primary ACC of the lung located peripherally within lung parenchyma is an even rarer event. To the best of our knowledge, this is the first case of primary peripheral pulmonary ACC preoperatively diagnosed by fine needle aspiration cytology (FNAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Lacrimal gland is the other primary site in this region 14 . Nonsalivary primary sites were lung, trachea, breast and paravaginal skin and soft tissue in our study as they were reported 6‐9,23,24 . The cytomorphology of all cases both salivary and nonsalivary was identical.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Lacrimal gland is the other primary site in this region 14 . Nonsalivary primary sites were lung, trachea, breast and paravaginal skin and soft tissue in our study as they were reported 6‐9,23,24 . The cytomorphology of all cases both salivary and nonsalivary was identical.…”
Section: Discussionsupporting
confidence: 59%
“…14 Nonsalivary primary sites were lung, trachea, breast and paravaginal skin and soft tissue in our study as they were reported. [6][7][8][9]23,24 The cytomorphology of all cases both salivary and nonsalivary was Our study showed that this tumor occurred primarily and mostly in major and minor salivary glands (50% of cases), followed by head and neck region (15% of cases). The lymph nodes (10% of cases) were Table 3 for details.…”
Section: Discussionmentioning
confidence: 56%
“…The focal sieve-like structure of pleomorphic adenoma may resemble PACC, but distinguishing between the two can be done based on cell morphology, structural pattern, interstitial composition, and immunohistochemistry. Pleomorphic adenomas share a common histogenesis at the intercalated duct level and often exhibit a combination of neoplastic basaloid cells [ 32 ]. Diagnosis of pleomorphic adenomas was unlikely as this benign tumor typically has a Ki-67 value of less than 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Cytological findings include cohesive clusters of repetitive medium-sized cells, with scant cytoplasm and uniform, small, hyperchromatic nuclei containing a finely granular, evenly distributed chromatin (Figures 2C–F). Tumor cells are often arranged around a central core of homogeneous myxoid material, or form three-dimensional, “ball-like” clusters (Table 4) (10–13, 15, 1922, 24, 26, 33). All of these features that recapitulate the histopathology of AdCC are helpful in correctly orienting the cytological diagnosis of this neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…All of these features that recapitulate the histopathology of AdCC are helpful in correctly orienting the cytological diagnosis of this neoplasm. Sometimes, isolated hyaline globules can be observed (7, 20, 24, 26); singly dispersed cells are present on some smears (11, 26). The basement membrane material, forming globules that have a light blue appearance on PAP stain and bright magenta on MGG stain, is the characteristic feature of AdCC; diagnostic difficulties arise when they are not present on cytological material, as the pattern could mimic carcinoid tumor, SCLC, NSCLC, and reserve cell hyperplasia (19).…”
Section: Discussionmentioning
confidence: 99%